Mineral Commodity Summaries 1995 - Significant Events, Trends, And Issues - The Mineral Sector Of The U.S. Economy (The National Institute for Occupational Safety and Health (NIOSH), 1995)
A stronger U.S. economy stimulated the domestic mineral sector in 1994. Metals demand was spurred by robust U.S. motor vehicle sales, while demand for major industrial minerals rose in response to highway and building construction. Domestic mineral and material demand is expected to increase in 1995, particularly if interest rates do not restrain the building industry and international monetary exchange rates remain advantageous to U.S. automobile manufacturers. Additional information on events, trends, and issues in the mineral and material sector is presented below and in the commodity sections that follow. Overall Performance Processed materials of mineral origin produced in the United States during 1994 increased to an estimated value of $360 billion. Domestic output of raw nonfuel minerals in 1994 was estimated at $34 billion, about 6% more than that of 1993. The value of U.S. minerals production has increased in 29 of the last 34 years.